A rare case of inflammatory myofibroblastic tumor presenting with pneumothorax - Vešović, Radomir; Radovanović, Dragan; Stojšić, Jelena; Popović, Marko; Moromila, Marina (Vojnosanitetski pregled, 2021)
Introduction. An inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal tumor of unclear etiology, which demonstrates myofibroblastic differentiation accompanied by inflammatory cells. IMT is a frequent primary lung tumor in children and is of nonspecific symptomatology and imaging methods. Its definitive diagnosis requires histopathology and immunohistochemistry of the tissue sample obtained after a rigid bronchoscopy or after complete surgical resection. Case report. A 16-year-old male patient was admitted to our clinic for further treatment of IMT verified by rigid bronchoscopy. He had previously been treated at another institution for left-sided pneumothorax with thoracic drainage. Since it had not resulted in lung reexpansion, a chest computed tomography was performed followed by rigid bronchoscopy that eventually established IMT diagnosis in the distal part of the left main bronchus. Since the tumor surrounded the left lobar carina and infiltrated the pulmonary artery, pneumonectomy was undertaken. Its morphology and immunoprofile determined the IMT diagnosis. Four years after surgical resection, the patient showed no recidivism of the illness. Conclusion. IMT is one of the most frequent primary lung tumors in children and needs to always be suspected upon. Pneumothorax can appear as an IMT manifestation. Its occurrence could be the consequence of either a visceral pleura lesion in case of peripheral tumors or a ball valve mechanism in case of endobronchial tumors. Definitive diagnosis of IMT requires not only histopathology but also immunohistochemical analysis. Complete surgical resection results in the best survival rates. Further monitoring of patients is necessary due to the risk of recurrence.
Keywords: adolescenti; dijagnoza; pluća, neoplazme; pneumotoraks; pneumonektomija; lečenje, ishod